(untitled) (Perner’s Contacts, 2011)
In general concept passenger transport in the relation to the region holds an important role because it has got a positive effect for its development. It can be seen especially in the growth and development of all practicable activities that also reflects the economic development of the region and contributes to a physical acquirement of the basic aim of transport to free movement of persons. The main problem solved in this paper consists in the prediction of the development of basic indicators of transport of enterprises with activity in road transport according to the evaluation of last trends and implementation of models, planning and prognostics.